Optimalisasi Promosi dan Manajerial di Kampung Wisata Pelangi Kota Semarang - Rizkiyanti, Dhania Febri; Vitrianto, Primantoro Nur; Damiasih (Jurnal Manajemen Perhotelan dan Pariwisata, 2024)
The city of Semarang has significant tourism potential. However, to optimize the promotion and management of Kampung Wisata Pelangi, Semarang, support from various parties is needed to maximize sustainable tourism potential. Located in the Old Town, this village has become an attractive destination thanks to government initiatives and local community participation. However, there are still challenges regarding infrastructure, waste management, and the quality of tourism services. Through qualitative methods and literature review, this study identifies promotional strategies using social media and the development of an integrated official website to increase visibility and the number of tourist visits. Additionally, effective management approaches are necessary to address infrastructure and waste management challenges, as well as to improve service quality. It is hoped that the results of this research can provide practical guidance for managers and stakeholders in optimizing the potential of Kampung Wisata Pelangi as a superior and sustainable tourist destination.